2019
DOI: 10.5194/acp-19-3589-2019
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the seasonal and geographical variability in tropospheric ozone, stratospheric influence and recent changes

Abstract: Abstract. The stratospheric contribution to tropospheric ozone (O3) has been a subject of much debate in recent decades but is known to have an important influence. Recent improvements in diagnostic and modelling tools provide new evidence that the stratosphere has a much larger influence than previously thought. This study aims to characterise the seasonal and geographical distribution of tropospheric ozone, its variability, and its changes and provide quantification of the stratospheric influence on these me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 102 publications
(159 reference statements)
3
39
0
Order By: Relevance
“…At this altitude a considerable inter-annual variability is visible in the observations, which appears to be well captured by the reanalysis products, with temporal correlations in the order R=0.85 (for TCR-1) to R=0.92 (CAMS-REAN). Also both the observations and reanalyses indicate an upward trend of tropospheric ozone in the UTLS, as also confirmed by Williams et al, (2019).…”
Section: Time Series Of Regionally Averaged O 3 Biases At Multiple Alsupporting
confidence: 75%
“…At this altitude a considerable inter-annual variability is visible in the observations, which appears to be well captured by the reanalysis products, with temporal correlations in the order R=0.85 (for TCR-1) to R=0.92 (CAMS-REAN). Also both the observations and reanalyses indicate an upward trend of tropospheric ozone in the UTLS, as also confirmed by Williams et al, (2019).…”
Section: Time Series Of Regionally Averaged O 3 Biases At Multiple Alsupporting
confidence: 75%
“…Deep folds extending down to the lower troposphere and occasionally to the ground surface may lead to irreversible mixing of stratospheric air into the troposphere and thus to chemical composition changes (Cristofanelli et al, 2006;Akritidis et al, 2010;Lin et al, 2015;Knowland et al, 2017). During recent years, several modelling studies indicated that the stratospheric contribution to tropospheric and near-surface background ozone may be of greater importance than previously anticipated (Zhang et al, 2011;Lin et al, 2012;Zanis et al, 2014;Lefohn et al, 2014;Akritidis et al, 2016;Williams et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Both short-and long-term exposure to tropospheric ozone has a negative impact on the health of people, animals, plants, and entire ecosystems. According to the latest research by Williams et al (2019), tropospheric ozone concentrations are currently increasing in most countries of the world, particularly in the Northern Hemisphere [57].…”
Section: Resultsmentioning
confidence: 99%